Statins can suppress DC‐mediated Th2 responses through the repression of OX40‐ligand and CCL17 expression. Issue 11 (11th July 2019) - Inagaki‐Katashiba, Noriko; Ito, Tomoki; Inaba, Muneo; Azuma, Yoshiko; Tanaka, Akihiro; Phan, Vien; Kibata, Kayoko; Satake, Atsushi; Nomura, Shosaku
Abstract: DCs and epithelial cell‐derived thymic stromal lymphopoietin (TSLP) have pivotal roles in allergic inflammation. TSLP stimulates myeloid DCs to express OX40‐ligand (OX40L) and CCL17, which trigger and maintain Th2 cell responses. We have previously shown that statins, which are HMG‐CoA reductase inhibitors, have the ability to suppress type I IFN production by plasmacytoid DCs. Here, we extended our previous work to examine the immunomodulatory effect of statins on allergic responses, particularly the TSLP‐dependent Th2 pathway induced by myeloid DCs. We found that treatment of TSLP‐stimulated DCs with either pitavastatin or simvastatin suppressed both the DC‐mediated inflammatory Th2 cell differentiation and CRTH2 + CD4 + memory Th2 cell expansion and also repressed the expressions of OX40L and CCL17 by DCs. These inhibitory effects of statins were mimicked by treatment with either a geranylgeranyl‐transferase inhibitor or Rho‐kinase inhibitor and were counteracted by the addition of mevalonate, suggesting that statins induce geranylgeranylated Rho inactivation through a mevalonate‐dependent pathway. We also found that statins inhibited the expressions of phosphorylated STA6 and NF‐κB‐p50 in TSLP‐stimulated DCs. This study identified a specific ability of statins to control DC‐mediated Th2 responses, suggesting their therapeutic potential for treating allergic diseases. Abstract : A cellular target in the cascade of allergic inflammation by which statins act as an inhibitor of allergy. Statins inhibit OX40L and CCL17 inductions from DCs through a blockade of NF‐κB p50 and STAT6 activation, leading to an inhibitory effect on DC‐mediated Th2 responses in the upstream phase of the immunological allergic cascade.